Does Gender Influence Participation? Predictors of Participation in a Community Health Worker Diabetes Management Intervention with African-American and Latino Adults - Hawkins, Jaclynn (2013)
PURPOSE: The purpose of the study was to determine the effects of gender on participation in a community-based, culturally tailored diabetes lifestyle intervention, led by trained community health workers (CHW), and conducted with African Americans and Latinos with type 2 diabetes. METHODS: This study utilized data collected from 180 participants. Multivariable binary and cumulative logistic regression models were used to analyze associations between gender and race/ethnicity with study completion and participation in three aspects of the intervention: group classes, CHW home visits, and CHW-accompanied doctor visits. RESULTS: Among Latinos, men were less likely than women to complete the study, attend >x classes, and complete # CHW home visits. There were no gender differences in participation seen among African-Americans. CONCLUSIONS: Diabetes management interventions may need to adapt their designs to optimize retention and participation of Latino men. Among African American men, the CHW model may be promising. Reasons for low participation among Latino men should receive more study. Future studies should assess whether similar findings apply in other communities and populations.